Promise and betrayal : universities and the battle for sustainable urban neighborhoods - Gilderbloom, John Ingram (State University of New York Press, 2005)
"Traditionally, institutions of higher education have been viewed as the gateway to a better future, despite the fact that so many of the neighborhoods surrounding them have been filled with hopelessness and despair. In Promise and Betrayal, the authors want nothing less than to start a revolution in higher education, calling on partnerships between "town and gown" to create sustainable urban neighborhoods. John I. Gilderbloom and R.L. Mullins, Jr. detail how higher education institutions can play an important role in helping to revitalize our poor neighborhoods by forming partnerships with public, private, and nonprofit groups. They advocate leaving the "ivory tower" and supplying the community with expert knowledge as well as creative and technical resources."--Jacket